KARAKTERISTIK OPERASIONAL BRT (BUS RAPID TRANSIT) DI JALAN TEUKU UMAR BANDAR LAMPUNG SETELAH ADANYA PELEBARAN JALAN - Juwandi Yasa (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2013)
Trans bus bandar lampung as urban mass transit plays an important role for the government ofbandar lampung in addressing the problem of traffic congestion and heavy traffic at the rushhour. Trans bus existence bandar lampung also very helpful community of bandar lampung espe-cially for students, college students, employees and the general public in carrying out activities ofdaily activities by providing transportation that can provide a sense of security, comfortable, eco -nomical as well as save time. Trans bus operations simulation lampung on jalan teuku umar per-formed with some of the first scenario is the implementation of special BRT corridor and the sec-ond with the imposition of special BRT corridor by eliminating microbus / public transportation.Furthermore also seen the advantages and disadvantages of implementing BRT in full or partially.From the analysis of the two scenarios above simulation, we got the result that the applicationscenarios specifically BRT corridor by eliminating microbus / public transportation increases thelevel of service to the tanjung karang - rajabasa from D to C and to route rajabasa - tanjungkarang from E to D. Further analysis of the study is needed to determine the effectiveness of thisscenario if applied in these other BRT routes in order to attract both local and non-local investorsto invest in this mass transportation.